Enhancing Vocabulary Retention Through Personalized Learning: Evaluating the Impact of the "Baicizhan" App on students’ Long-Term Memory - Huang, Menglin; Vijayaratnam, Phawani; binti Hamdan, Norazrina; Shirzad, Shaghayegh; Barjesteh, Hamed (Forum for Linguistic Studies, 2025)
In the digital era, personalized learning has gained significant attention in the realm of English vocabulary acquisition. While numerous mobile applications claim to enhance vocabulary memory, empirical evidence regarding their actual effectiveness and user experiences remains limited. This study aims to systematically evaluate the Baicizhan app in improving English vocabulary retention, meeting the diverse needs of learners, and supporting long-term memory storage. This study utilizes Cognitive Load Theory, Motivation Theory, and Constructivist Learning Theory to explore how the Baicizhan app enhances vocabulary acquisition and long-term memory by optimizing cognitive processing, fostering learner engagement, and promoting active knowledge construction through personalized learning pathways and multimodal resources. Data were collected through interviews with fifteen diverse users, revealing that Baicizhan significantly enhances learner engagement, motivation, and vocabulary retention through its personalized and interactive features. The results suggest that the app is effective in promoting long-term memory consolidation, aligning with cognitive and metacognitive learning principles. However, to further improve its effectiveness across varied learning environments, the app should be optimized based on user feedback and specific learning profiles. This study provides both theoretical and practical insights for enhancing mobile-assisted language learning tools to improve education quality.